Manajemen Pendidikan Tasawuf dalam Mencapai Taqarub pada Allah bagi Santri di Pondok Pesantren Baiturrohmah Malang - Wahyudi Widodo (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Sufism is usually associated with traditional or rural societies. Because, although their culture is closer to Sufism, urban people ignore it. However, Sufism is sometimes considered a solution to the problem of spiritual awakening. It was a Sufism program at Pesantren Baiturohmah in Malang. Sufism that combines the teachings of nature and sharia is taught in this mixed stream. The research method used is qualitative or directly involved. The results obtained include: The idea of Sufism education at the Baiturrohmah Islamic Boarding School in Malang City is based on Islamic teachings that aim to achieve a harmonious balance between sharia (Islamic law) and the spiritual journey towards attaining closeness to God. 2) Sufism Education Management in achieving Taqarub to Allah for Santri is carried out in a program called khalwat which consists of four things, namely: a) The process of bai'at involves students joining pesantren and being taught the processes of tawasul and khlawat by their professors, Murshid. b) During this phase, students practice Khalwat and uzlah by isolating themselves from the public for 7 days. They also develop the quality of zuhud by completing sunnah and fasting rituals. c) give mahdah worship lessons with basic to upper and d) stay in the hut for seven days and are prohibited from interacting with outside.